Biocompatible Nutmeg Oil-Loaded Nanoemulsion as Phyto-Repellent - Mohd Narawi, Masturah; Chiu, Hock Ing; Yong, Yoke Keong; Mohamad Zain, Nur Nadhirah; Ramachandran, Muggundha Raoov; Tham, Chau Ling; Samsurrijal, Siti Fatimah; Lim, Vuanghao (Frontiers in Pharmacology, 2020)
Plant essential oils are widely used in perfumes and insect repellent products. However, due to the high volatility of the constituents in essential oils, their efficacy as a repellent product is less effective than that of synthetic compounds. Using a nanoemulsion as a carrier is one way to overcome this disadvantage of essential oils. Nutmeg oil-loaded nanoemulsion (NT) was prepared using a high speed homogenizer and sonicator with varying amounts of surfactant, glycerol, and distilled water. Using a phase diagram, different formulations were tested for their droplet size and insect repellent activity. The nanoemulsion containing 6.25% surfactant and 91.25% glycerol (NT 6) had the highest percentage of protection (87.81%) in terms of repellent activity among the formulations tested for the 8 h duration of the experiment. The droplet size of NT 6 was 217.4 nm, and its polydispersity index (PDI) was 0.248. The zeta potential value was –44.2 mV, and the viscosity was 2.49 Pa.s at pH 5.6. The in vitro release profile was 71.5%. When the cytotoxicity of NT 6 at 400 µg/mL was tested using the MTS assay, cell viability was 97.38%. Physical appearance and stability of the nanoemulsion improved with the addition of glycerol as a co-solvent. In summary, a nutmeg oil-loaded nanoemulsion was successfully formulated and its controlled release of the essential oil showed mosquito repellent activity, thus eliminating the disadvantages of essential oils.